Competency, Motivation, and Supervision Technique Strong Predict to Completeness of Nursing Documentation - Wongso, Erni Suryani; Tahjoo, Anastina; Nofierni, Nofierni (Alta Dharma Publisher, 2024)
Background: The inconsistency in the results of previous research conducted regarding competency, motivation and completeness of nursing documents motivated the research was carry out. Objective: This study aimed to examine empirical evidence regarding the mediation of disclosure of supervision techniques on competence and motivation on the completeness of nursing documentation. Method: A quantitative study with the cross-sectional approach was conducted in this study. This study was conducted in the dr. Achmad Diponegoro hospital. Forty-five respondents were involved in this study which is selected using the purposively sampling. We applied the path analysis to examine the association between competency, motivation, and supervision technique with completeness of nursing documentation. Result: The research results show empirical evidence that simultaneously competence and motivation have a positive and significant effect on supervision techniques. Competence, motivation and supervision techniques have a positive and significant effect on the completeness of nursing documentation. However, supervision techniques were not successful in mediating the influence of competence and motivation on the completeness of nursing documentation because the direct influence was greater than the indirect influence. Implication: The implication of the research is that management must provide training and provide facilities so that health workers can improve their competence and hold activities or awards for health workers who have good performance in recording nursing documents so that their motivation increases